Virtual Reality-Based Learning Media Design Training - Astari, Tri (Al-Qalam Institute, 2022)
This activity aims to facilitate the design of learning media based on Virtual Reality (VR) for educators to be able to present innovative learning in the classroom. The method used in this mentoring activity consists of four stages: Asset Based Community Development called